Budget travel - Morrison, Geoffrey (Travel writer) (--For dummies., 2024)
Budget Travel For Dummies will help you plan your next vacation and make it affordable, with tips on how to maximize your budget and squeeze amazing experiences out of every penny. Written by a travel expert who has visited 60 countries across 6 continents, this book will help you find the best deals, including cheap flights and accommodations. You'll learn how to pick a destination, set and stick to a budget, minimize bank and credit card fees, and manage health and travel insurance. For the adventurer within you, this guide is full of tips on traveling without a plan, living for months with just carry-on luggage, and staying flexible in case you need to change your plans. Yes, you can afford that bucket-list trip.